PEMBERDAYAAN MASYARAKAT MELALUI TEKNOLOGI HILIRISASI KOMODITAS TOMAT UNTUK MENINGKATKAN PENDAPATAN RUMAH TANGGA DI DESA KALI PADANG - Mohamad Zulkarnain Yuliarso; Basuki Sigit Priyono; Ridha Rizki Novanda (Universitas Bengkulu, 2020)
Kali Padang village has a big problem, namely the price of tomatoes at the farmer's level which is very low during the harvest season. This condition is further exacerbated by the nature of tomatoes that are easily damaged, causing a decrease in quality and economic value. The introduction of tomato commodity downstream activities is needed by empowering the housewives of farmers. So the purpose of the purpose of this activity is to: 1) Introduce the technology of making tomato sauce to farm women groups, 2) Introduce how to do hygienic tomato packaging, 3) Introduce how to determine the cost of production and the selling price of tomato sauce processed, and 4) Carry out one element of Higher Education Tri Dharma, namely Community Service. The service method is done by counseling, introducing technology and applying technology. This dedication activity has introduced the technology of making tomato sauce to farm women's groups. Carrying out these service activities in general can provide knowledge and skills of processing tomatoes into tomato sauce. The packaging skills of a farm woman increase and how to do hygienic tomato sauce packaging. The ability to determine cost of goods is also done well. There has been a change in knowledge, attitudes and skills of the target group after the science and technology service activities were carried out.